THE EFFECT OF BIRTHING BALL ON PAIN 1st TIME OF LABOR IN PRIMIPARA MOTHERS AT PMB AMALIA TEMON VILLAGE - Ida Nuraini; Anggita Septyani Permatasari; Rosmala Kurnia Dewi (Jurnal Profesi Bidan Indonesia, 2024)
Background; Labor pain is a process of protection from the mother's body to notify her of danger signs and will increase sympathetic nerve activity, then cause changes in heart rate pressure, breathing problems, muscle tension and stress. Handling to treat labor pain in pharmacology is in the form of analgesic drugs, while non-pharmacological treatments such as messages, use of birthing balls, touch, relaxation, warm compresses and cold compresses use of arromatherapy, breathing control, positioning, music therapy, hypnotherapy, and acupuncture. The research objective was to determine the effect of the birthing ball on the pain of the first stage of labor in primiparous women. Methodology; This type of quantitative research with quasi-experimental and research design using two group pretest posttest design. Population All primiparous pregnant women in February-April at the end of the month were 54 mothers giving birth. The sample consists of 14 samples for each control and treatment group from the calculation of the Lameshow formula. Data analysis using the Mann Whitney Test. Results; The level of labor pain in the treatment group who was given the birthing ball at BPM Amalia Temon Village in 2022 was mostly controlled by 12 respondents (85.7%) of severe pain and after being given the birthing ball the most moderate pain was 8 respondents (57.1%) and mild pain 6 respondents (42.9%). The level of labor pain in the control group who was not given the birthing ball at BPM Amalia Temon Village in 2022 was mostly controlled by 12 respondents (85.7%) of severe pain and after being given the birthing ball the most moderate pain was 10 respondents (71.4%) ). Conclusion; There was an effect of the birthing ball on the first stage of labor pain in primiparous women at BPM Amalia Temon Village (p=0.000)